APPLICATION OF PREFERRED ISLAMIC LEGAL MAXIMS ON THE PRONOUNCEMENT OF TALAK OUTSIDE THE COURT IN MALAYSIA: A BRIEF DISCUSSION - Nur Sarah Tajul Urus; Alias Azhar , (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This article discusses the application of Islamic legal maxims on the pronouncement of talak outside the court in Malaysia. The purpose of this article is to identify the preferred Islamic legal maxims by judges for divorce cases. The concept of divorce was analysed to see preferred Islamic legal maxims as an essential element in the submission of each case in order to study the role of preferred Islamic legal maxims as an argument in Islamic law and to examine the position of the writing of judgment in Islam. This study was based on a qualitative approach with two main methodologies, namely, data collection and data analysis methods. Data were gathered through document analysis and interviews over four months in 2017 in the states of Kedah and Kelantan in Malaysia. This study also examined the position and importance of judgment writing in Islamic law by interviewing two academicians and four legal practitioners to obtain information on the application of preferred Islamic legal maxims in judgments and the practice of judgment writing in divorce cases in Malaysia. Data were analysed by applying the content analysis method. This method was also used to analyse the documents obtained from the respondents to extract detailed information on the application of preferred Islamic legal maxims in divorce cases. The results of the study suggest that legal maxims play a significant role in deriving rulings and supporting submissions in dealing with Shariah cases. The preferred Islamic legal maxims, which contain the Maqasid al-Shariah values, must be in parallel with al-Quran and al-Sunnah. Given the prevalence of family issues today, it is hoped that society can entrust Maqasid al-Shariah in dealing with divorce cases. Cooperation between Shariah judges and lawyers helps in developing innovative elements encompassing religious and legal aspects. In this global era, the application and trend of Islamic legal maxims will have a tremendous impact on religious and institutional courts, in particular, Shariah Courts at the national level. This application is aimed at eliminating confusion among the parties involved, specifically, and the Muslim community, in general.